The Perspective of Muslim Minority Tenth-Grade Students at SMANSA on Religious Differences in the School Environment - Ma'shumah Syamsir; Najamuddin Najamuddin; Alimin Alwi (Asosiasi Dosen Muda Indonesia, 2025)
This research aims to explore the Muslim minority's perspective on religious differences in the SMAN 1 environment. The research method used is a phenomenological qualitative research method with semi-structured interview techniques and participant observation, the number of informants is two people, one man and one woman who were chosen purposively. Data analysis using the Miles & Huberman interactive model. The research results show five main themes: (1) ambivalent perceptions of diversity, (2) dynamics of interfaith interactions, (3) school support for religious activities, (4) variations in the role of teachers in building tolerance, and (5) expressions of religious identity that are not always accepted equally. These findings confirm that tolerance in schools is formed through social interaction, the role of teachers, and institutional culture. This research shows that students' experiences in interacting with religious diversity in schools are complex and influenced by social dynamics that occur in daily activities. Students generally understand that diversity is part of school life, but their perceptions and experiences vary, ranging from a sense of comfort and mutual respect to tension during discussions related to religion. These findings emphasize that tolerance is not formed automatically in a diverse environment, but is a process that requires institutional support, healthy social relations, and the role of teachers in socializing diversity.